2016
DOI: 10.1183/13993003.00359-2016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lung cancer worldwide

Abstract: Lung cancer is the most frequent malignant neoplasm in most countries, and the main cancer-related cause of mortality worldwide in both sexes combined.The geographic and temporal patterns of lung cancer incidence, as well as lung cancer mortality, on a population level are chiefly determined by tobacco consumption, the main aetiological factor in lung carcinogenesis.Other factors such as genetic susceptibility, poor diet, occupational exposures and air pollution may act independently or in concert with tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
416
2
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 682 publications
(512 citation statements)
references
References 99 publications
13
416
2
20
Order By: Relevance
“…There is a possibility that this combination may be more common than initially considered, if endoscopically treatable early colon cancer is taken into consideration. It is generally accepted that cigarette smoking plays an important role in lung carcinogenesis (4). In addition, epidemiological data suggested that obesity is associated with an increased risk of colon cancer (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a possibility that this combination may be more common than initially considered, if endoscopically treatable early colon cancer is taken into consideration. It is generally accepted that cigarette smoking plays an important role in lung carcinogenesis (4). In addition, epidemiological data suggested that obesity is associated with an increased risk of colon cancer (10).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologically, it has been suggested that cigarette smoking is closely associated with an increased risk of cancer in various organs, including the lung and the colon (4,5). Lung cancer is primarily known to be associated with upper aerodigestive tract cancer, but its association with gastrointestinal cancer should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent work of researchers worldwide has focused over the identifiable risk factors in lung cancer and the possibility to influence some of them. Genetic factors, tobacco smoking, diet and alcohol, chronic pulmonary inflammation, ionizing radiation, occupational exposure, environmental pollution (mainly due to tobacco smoke, radon and asbestos), and other risk factors (hormones, underweight) have been largely discussed [3,5]. Moreover, the World Cancer Research Fund/ American Institute for Cancer Research Second Expert Report Panel judged that arsenic in drinking water and β-carotene supplements have increased the risk of lung cancer; but consuming fruits and food containing carotenoids probably has protective consequences [1].…”
Section: The Risky Diet and Lifestylementioning
confidence: 99%
“…Despite of being a highly preventable disease, lung cancer remains the most common cancer in the world in terms of new cases, 1.8 million in 2012 (12.9% in total), and mortality [1][2][3]. It accounts for 19.4% of all cancer deaths, being the main cancer-related cause of mortality regardless the gender [2].…”
Section: Introductionmentioning
confidence: 99%